Mitochondria in Acetaminophen-Induced Liver Injury and Recovery: A Concise Review - Anup Ramachandran; Hartmut Jaeschke (Livers, 2023)
Mitochondria are critical organelles responsible for the maintenance of cellular energy homeostasis. Thus, their dysfunction can have severe consequences in cells responsible for energy-intensive metabolic function, such as hepatocytes. Extensive research over the last decades have identified compromised mitochondrial function as a central feature in the pathophysiology of liver injury induced by an acetaminophen (APAP) overdose, the most common cause of acute liver failure in the United States. While hepatocyte mitochondrial oxidative and nitrosative stress coupled with induction of the mitochondrial permeability transition are well recognized after an APAP overdose, recent studies have revealed additional details about the organelle’s role in APAP pathophysiology. This concise review highlights these new advances, which establish the central role of the mitochondria in APAP pathophysiology, and places them in the context of earlier information in the literature. Adaptive alterations in mitochondrial morphology as well as the role of cellular iron in mitochondrial dysfunction and the organelle’s importance in liver recovery after APAP-induced injury will be discussed.